Clinical challenges associated with bortezomib therapy in multiple myeloma and Waldenströms Macroglobulinemia - LAUBACH, JACOB P. (2009)
Rapid development of the small molecule proteasome inhibitor bortezomib has yielded important clinical benefit for patients with multiple myeloma. Early phase clinical trials suggest the agent has similar efficacy in Waldenströms Macroglobulinemia. Optimization of bortezomib-based therapy, though, requires an understanding of the various challenges associated with use of the drug. This review highlights the rationale for bortezomib therapy in patients with multiple myeloma and Waldenströms Macroglobulinemia, mechanisms of bortezomib resistance, important therapy-related side effects, and new directions for the use of proteasome inhibitors in these disorders.